EXTH-13. COMBINED TARGETING OF TELOMERASE REVERSE TRANSCRIPTASE AND METABOLISM ABROGATES GLIOBLASTOMA PROLIFERATION IN VIVO. (14th November 2022) - Batsios, Georgios; Tran, Meryssa; Gillepspie, Anne Marie; Taglang, Celine; Viswanath, Pavithra
Abstract: Telomerase reverse transcriptase (TERT) is essential for tumor immortality. Since TERT is silenced in normal cells, it is an attractive therapeutic target and the TERT inhibitor 6-thio-2'-deoxyguanosine (6-thio-dG) is in clinical trials for gliomas. However, there is a lag period following TERT inhibition before tumor shrinkage is observed. Novel strategies that can be combined with TERT inhibition to enhance anti-tumor activity are sorely needed. We previously demonstrated that TERT increases expression of the alanine transporter ASCT2 in gliomas, an effect that could be non-invasively monitored using hyperpolarized 13 C imaging of alanine metabolism (Viswanath et al., Nature Communications, 2021). The goals of the current study were to determine whether combined inhibition of TERT and ASCT2 inhibits GBM growth and to assess the ability of hyperpolarized [1- 13 C]-alanine to monitor treatment response. Our results indicated that, while both the TERT inhibitor 6-thio-dG and the ASCT2 inhibitor V-9302 individually inhibited viability, the combination of 6-thio-dG and V-9302 maximally inhibited cell viability in the patient-derived GBM1 and GBM6 models. In line with the effect on cell viability, while both compounds reduced lactate production from hyperpolarized [1- 13 C]-alanine, the combination of 6-thio-dG and V-9302 resulted in the highest inhibition of lactate production in both models. Importantly, treatment of rats bearing orthotopic GBM6 tumors with a combination of 6-thio-dG and V-9302 caused tumor shrinkage, an effect that could be visualized by magnetic resonance imaging by day 21 after treatment. Furthermore, lactate production from hyperpolarized [1- 13 C]-alanine was significantly reduced at day 7 after treatment with 6-thio-dG and V-9302, when anatomical alterations were absent. Collectively, our results indicate that simultaneously targeting TERT and ASCT2 provides a novel therapeutic opportunity for GBMs and that hyperpolarized [1- 13 C]-alanine serves as a companion agent for imaging early response to therapy. Our findings pave the way for precision therapy and response assessment for GBM patients.